Un environnement multimédia privilégiant l'expression en langage naturel, pour des activités éducatives de type piagétien - Élisabeth Godbert (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This paper deals with the development of educational software, which proposes, in a multimedia, multimodal and reactive environment favoring natural language expression, piagetian games designed for natural language learning. In such systems, each exercise brings into play a micro-world of graphic objects on which the user can act (for example to modify, move or withdraw the objects), by composing natural language queries to which the system gives an answer. We present a software of this type, that has been designed and implemented these last years. We firstly describe the educational objectives and the functionality of the software, then the natural language processing system which is used in it. Finally we describe the set of components that structures knowledge modeled, articulated and managed in order to carry out this educational system.